Comparison of Curriculum and Learning Methods in Indonesia and Singapore - Nichlatul Maula; Ahmad Rifai; Putri Damayanti (PT Publikasiku Academic Solution, 2025)
This article presents an in-depth comparison of the curriculum and learning methods in Indonesia and Singapore. This study aims to compare the curriculum and learning methods applied in Indonesia and Singapore. The research method used is qualitative research with verbal descriptions, in the process, the data obtained comes from various methods such as literature review, literature review, and information search through the internet. From this research, several data were obtained, namely the Independent Curriculum emphasizing flexibility, project-based learning, and the formation of student character through the Pancasila Student Profile. On the other hand, Singapore's curriculum is more structured and standardised, with a focus on 21st century skills, and strong utilization of educational technology. Differences are also seen in the learning method, the Independent Curriculum has begun to implement active learning models such as Project Work, Problem Based Learning, and Inquiry Training which emphasizes the formation of student character and competence. Meanwhile, Singapore has systematically implemented methods such as Project Based Learning, Teach Less Learn More, Technology-Enhanced Learning and Flipped Classroom. Significant differences can be seen in the level of system readiness and utilization of educational technology, where Singapore excels in the curriculum and the implementation of adaptive and sustainable learning methods. This research is expected to make an academic and practical contribution to the development of the national curriculum in Indonesia so that it is more adaptive, contextual, and able to improve the quality of student learning outcomes in a sustainable manner.